Toward understanding the balanced steady-state free precession signal intensity changes in cine cardiac magnetic resonance imaging: A preliminary evaluation in healthy subjects pre- and postcontrast - Dresselaers, Tom; De Keyzer, Frederik; Cernicanu, Alexandru; Bogaert, Jan; Gatehouse, Peter (Journal of cardiovascular magnetic resonance, 2025)
Although balanced steady-state free-precession (bSSFP) cines provide excellent contrast for morpho-functional cardiac evaluation, the fluctuating myocardial cine signal intensity (mcSI) is rarely used diagnostically. These mcSI fluctuations were related to through-plane motion but the impact of this motion remains unclear. We aim to characterize the mid-ventricular pre- and postcontrast bSSFP cyclic mcSI fluctuations in healthy subjects and compare these to Bloch simulations incorporating through-plane motion. Retrospectively-gated mid-ventricular short-axis cine bSSFP images from healthy subjects (n = 49) acquired at 1.5T pre- and early postcontrast were analyzed. First, the mcSI fluctuations during the heart cycle were determined and their timing compared to the radial myocardial motion. Next, pre- vs postcontrast differences were determined during systole, early-diastole, and late-diastole. Finally, Bloch simulations and acquisitions in a moving T1 phantom were performed to analyze the through-plane motion effect on the bSSFP and spoiled gradient echo (SGRE) mcSI. The bSSFP mcSI showed a three-peak pattern both pre- and postcontrast, corresponding to the contraction and relaxation phases. However, the mcSI peaks showed a time lag vs the times of maximum radial velocity that was larger for the systolic contraction than for the early or late-diastolic relaxation phases. In addition, the shape and amplitude of the systolic and early diastolic mcSI peaks changed significantly post- vs precontrast. Bloch simulations showed an in-vivo-like (regional) three-peak signal profile and similar changes for post- vs precontrast T1 levels. Finally, results in the moving phantom and accompanying simulations confirmed a slice-thickness–dependent time lag between the motion and mcSI profile in both bSSFP and SGRE. In healthy subjects before and after contrast, the bSSFP mcSI variation during the heart cycle is characterized by a three-peak pattern associated with the contraction and relaxation phases. However, the delays in timing of these peaks vs the myocardial motion, as well as the differences between pre- and postcontrast, vary with the stage of the heart cycle. Bloch simulations suggest that these mcSI fluctuations are largely determined by the regional through-slice motion. A better understanding of these motion-induced contrast mechanisms may be beneficial to methods exploiting bSSFP mcSI. [Display omitted]